Changes in landscape disturbance intensity of sloping land in mountainous areas and their relationship with ecosystem services - Huiqing Han; Xin Yu; Yuanju Jian (Nature Conservation)
The stability of landscapes on sloping land forms the foundation for ecological protection and sustainable development in mountainous regions. However, with the intensification of human activities, particularly in the complex mountainous areas of southwest China, the landscape patterns on sloping land have been severely disrupted. This study examines the spatiotemporal changes in landscape disturbance intensity on sloping land in Guiyang and their impact on ecosystem services. The findings show that, over the past 20 years, the overall landscape disturbance intensity has generally decreased, particularly between 2000 and 2010. However, disturbance intensity has increased in certain gradient zones, such as areas with slopes between 20–25 degrees. Meanwhile, ecosystem services have generally declined, especially in water yield and crop production, while carbon stock has slightly increased. The study reveals a significant spatial correlation between landscape disturbance intensity and ecosystem services, with varying relationships across different services. It emphasises the profound impact of human activities on landscape stability and ecosystem services, particularly in areas with steeper slopes. The contribution of this research lies in providing a scientific basis for sustainable landscape management and ecosystem service conservation in mountainous areas, highlighting the importance of mitigating human disturbance and strengthening ecological restoration.